IDENTIFIKASI RISIKO ERGONOMI PADA PEKERJA UD. SATRIA TAHUN 2021 - Mohamad Nurhamzah Ramadani; Merry Sunaryo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
UD. Satria is an industry engaged in the manufacture of sandals that has been in production since the 1980s, which is located in the Waru area, Sidoarjo. UD. Satria accepts the production of sandals according to demand such as children's sandals or adult sandals as well as being a distributor for big shops in Sidoarjo and also online shops. In running this sandal business industry, UD. Satria has 7 workers who work 8 hours per day and still use manual processes in their production. Which means it has the potential for musculoskeletal complaints. Observation and data collection carried out is primary data collection. Which is where the data obtained directly from the respondents. After the field survey, it was found that it was necessary to collect data on Musculoskeletal Disorders (MSDs) using a questionnaire using the Nordic Body Map (NBM) method and followed by measuring work posture using the RULA (Rapid Upper Limb Assessment) method. Many workers complain of back and neck pain, it can be caused by the wrong work posture. Therefore, an ergonomic risk assessment was carried out, with the aim of identifying the level of complaints of musculoskeletal disorders (MSDs). As well as making efforts to reduce the risk of MSDs complaints that can affect the productivity level of UD. Satria workers.